Industry-level wage bargaining : a partial rehabilitation ; the German experience - Bernd Fitzenberger; Wolfgang Franz (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
In order to reduce unemployment, it is often recommended that industry-level wage bargaining in Germany should be replaced by a more decentralized system. This paper provides a critical assessment of the current wage bargaining institutions and reexamines the case for a more decentralized system. Based on a theoretical model integrating Insider-Outsider aspects into the comparison, the unformly superior employment performance of a decentralized wage bargaining system is questioned. We conclude that, rather than solely trying to decentralize wage bargaining, a promising policy option may be to improve the skills of the unemployed by efficient labour market policies and to foster institutional reforms such that wage bargaining takes account of the long-run employment consequences of wage setting.
Keywords: J31; J51; 330; Centralization of Wage Bargaining; Union Preferences; Insider-Outsider Theory; Germany; Tarifpolitik; Lohnverhandlungen; Firmentarifvertrag; Insider-Outsider-Modell; Theorie; Deutschland